Pulmonary Embolism Secondary to Silicone Injection - Molina, Carolyn Frances; Retalis, Zachary Paul (International Journal of Medical Students, 2019)
Background: The use of silicone for synthetic enhancement in cosmetic procedures has been established for decades but is questionable in safety as it is associated with a range of possible complications. Incidental injection of this polymer into the venous system is not uncommon and can result in the formation of microemboli, which can travel to the lungs. This occurrence can result in a rapid decline of respiratory function and send a patient into severe acute distress. The Case: This report details a female patient presenting with hemoptysis, presumed to have severe pneumonia until her history of cosmetic treatment was revealed and correlated. Her rapid respiratory decline is followed in inflammatory response markers and radiograph imaging. Conclusion: A unique treatment approach with prone positioning was used and may play a key role in decreasing mortality in these patients. This report draws attention to the dangers of cosmetic enhancement and raises clinical awareness for associated complications.